Placebo-controlled trial of oral laquinimod in multiple sclerosis: MRI evidence of an effect on brain tissue damage. Issue 8 (12th September 2013) - Filippi, Massimo; Rocca, Maria A; Pagani, Elisabetta; De Stefano, Nicola; Jeffery, Douglas; Kappos, Ludwig; Montalban, Xavier; Boyko, Alexei N; Comi, Giancarlo; ,
Abstract : Objective: In A ssessment of Ora L L aquinimod in Pr E venting Pro GR ession in Multiple Scler O sis (ALLEGRO), a phase III study in relapsing-remitting multiple sclerosis (RRMS), oral laquinimod slowed disability and brain atrophy progression, suggesting laquinimod may reduce tissue damage in MS. MRI techniques sensitive to the most destructive aspects of the disease were used to further investigate laquinimod's potential effects on inflammation and neurodegeneration. Methods: 1106 RRMS patients were randomised 1:1 to receive once-daily oral laquinimod (0.6 mg) or placebo for 24 months. White matter (WM), grey matter (GM) and thalamic fractions were derived at months 0, 12 and 24. Also assessed were evolution of gadolinium-enhancing and/or new T2 lesions into permanent black holes (PBH); magnetisation transfer ratio (MTR) of normal-appearing brain tissue (NABT), WM, GM and T2 lesions; and N-acetylaspartate/creatine (NAA/Cr) levels in WM. Results: Compared with placebo, laquinimod-treated patients showed lower rates of WM at months 12 and 24 (p=0.004 and p=0.035) and GM (p=0.004) atrophy at month 12 and a trend for less GM atrophy at month 24 (p=0.078). Laquinimod also slowed thalamic atrophy at month 12 (p=0.005) and month 24 (p=0.003) and reduced the number of PBH at 12 and 24 months evolving from active lesions (all p<0.05). By month 24, MTR decreased significantly in NABT (p=0.015), WM (p=0.011) and GM (p=0.034) in placebo-treated patients, but not in laquinimod-treated patients. WM NAA/Cr tended to increase with laquinimod and decrease with placebo at 24 months (p=0.179). Conclusions: Oral laquinimod may reduce (at least in the initial phase of treatment) some of the more destructive pathological processes in RRMS patients. Trial registration: The ALLEGRO trial identifier number with clinicaltrials.gov is NCT00509145 .